Voices of Women in the Arab Spring - Abdullatif, Amna (JSSE - Journal of Social Science Education, 2013)
This paper is an attempt to analyse the new and exciting times occurring currently in the Middle East. I will be examining the role of women during the Arab Spring by taking a social constructivist position. As well as this I aim to find analyses in Islamic feminist literature which deals with the issue of religion, gender and patriarchy within specific cultural and religious backgrounds. This will be complimented with a community psychological approach by assessing the issues of marginalization, concientization and empowerment presented by the media articles under analysis written by female Arab journalists, bloggers and activists.